Revision Anterior Cruciate Ligament, Lateral Collateral Ligament Reconstruction, and Osteochondral Allograft Transplantation for Complex Knee Instability - Peebles A.M. (2023)
Anterior cruciate ligament (ACL) injuries rarely occur as an isolated event and often include associated meniscal, subchondral bone, and collateral ligament injuries. Concomitant pathology frequently complicates primary and revision ACL reconstruction and must be addressed to ensure comprehensive diagnosis and treatment. In this Technical Note, we describe our method for treatment of complex knee instability following multiple failed ACL reconstruction using a multiligament reconstruction technique with an osteochondral allograft transplantation to the lateral femoral condyle. This comprehensive repair technique restores the anatomic load bearing forces of the cruciate and collateral ligaments and promotes biological repair through incorporation of cartilage resurfacing to ultimately achieve optimal kinematics of the knee joint.